Teaching Southeast European History in Croatia: Challenges and Prospects for the Future - Štefanec, Nataša (2004)
The lecture presented methods, approaches and thematic focuses of history teaching at Croatian universities, proposing various options for the enhancement of teaching and scientific co-operation among South-east European universities, and emphasizing the need of regional and, above all, transnational, approach to history teaching and research.
Projekt MZOS
ENG